Teachers’ perspectives on using differentiated instruction in the mixed ability classroom at one government primary school - Sutherland-Kalisingh, Golda (My University, 2017)
Through the lived experiences of five teachers, this study investigated the use of differentiated instruction (DI) in the classroom at a government primary school in Trinidad and Tobago. The teachers were drawn from levels ranging from Infants to Standard 4. Data were collected through interviews. Overall, the findings revealed that while the teachers might have a desire to practice a greater degree of DI in the classroom, there is the risk that they could become easily distracted if the appropriate resources and environment were not made available to facilitate the activities involved in its employment.
Keywords: Primary school teachers; Teacher attitudes; Ability grouping; Classroom methods; Trinidad and Tobago